RANCANG BANGUN SISTEM PELAPORAN PRAKTEK KERJA LAPANGAN (PKL) PESERTA DIDIK BERBASIS WEBSITE DI UPT SMK NEGERI 7 JENEPONTO - Miftahur Risky Jufri; Hendra Jaya; Purnamawati (UNM Journal of Technology and Vocational, 2023)
This study aims to; 1) determine the results of the development of a reporting system for field work practice (PKL) of students at UPT SMKN 7 Jeneponto. (PKL) students at UPT SMKN 7 Jeneponto, 2) knowing the validation of the reporting system for student field work practice (PKL) at UPT SMKN 7 Jeneponto, 3) knowing the practicality of the reporting system.field work practice (PKL) students at UPT SMKN 7 Jeneponto, 3) find out the practicality of the the reporting system for student field work practices (PKL) at UPT SMKN 7 Jeneponto, 4) knowing the effectiveness of the reporting system for student field work practices at UPT SMKN 7 Jeneponto and 5) knowing the effectiveness of the reporting system for student field work practices at UPT SMKN 7 Jeneponto. 7 Jeneponto and 5) find out the user's response after using the reporting system. reporting system for student field work practices (PKL) at UPT SMKN 7 Jeneponto. This research using the Research and Development (R&D) research method with the prototyping development model.prototyping development model. The data collection technique uses interviews, questionnaires and software which measures the quality of the software that has been developed. The research results show1) the PKL reporting system or SIP-PKL is a system used to assist the reporting of PKL at SMKN 7 Jeneponto which consists of 4 user accesses, namely admin, teacher, and teacher. PKL reporting at SMKN 7 Jeneponto which consists of 4 user accesses, namely admin, teacher, field supervisors and students, 2) system testing using ISO 25010 in the aspect of functionality suitability with the test results are valid which are tested by experts, 3) practicality SIP-PKL refers to testing the usability and reliability aspects where the usability test results show a percentage of 95.7% from 6 aspects.usability test results show a percentage of 95.7% of the 6 aspects of testing and the results of reliability testing using WAPT 10.1 software.WAPT 10.1 software obtained a value of 98.46% so that it fulfills the reliability aspect, 4) portability and performance efficiency testing is used to measure the effectiveness of a system where 100% results are obtained in portability testing. system where 100% results were obtained in portability testing on desktop and mobile environments and grate B (80-89). mobile environment and grate B (80-89%) in performance efficiency testing with GTMetrix tools, and 5) SIP-PKL is used to measure the effectiveness of a system. 5) SIP-PKL that has been developed gets good feedback from users.